Solutions by everydaycalculation.com
How to solve 2x + 3 = 3x + 4? Get the answer and stepwise instruction to solve linear equation in one one variable 𝒙.
We have 2x + 3 = 3x + 4
First, we move the x terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.
Transposition is a faster method and combines the following two steps, were we to solve the equation by:
i) Subtracting 3 from both sides
ii) Subtracting 3x from both sides
Therefore, 2x - 3x = 4 - 3
or, -x = 1
Next, divide both sides by -1, which is the coefficent of xNote: if a = b, then a ÷ c = b ÷ c
-1x/-1 = 1/-1
x = 1/-1 or, x = -1